Measuring sustainable intensification in smallholder agroecosystems: A review - Smith, A.; Thorne, Peter J.; Snapp, Sieglinde S. (International Livestock Research Institute, 2015)
In the sustainable intensification (SI) of smallholder agroecosystems, researchers and farmers collaborate to produce more food on land currently in cultivation, secure wellbeing in the present day, and bolster ecosystem services to sustain agricultural productivity into the future. In recent years there has been debate in the SI literature about the meaning and boundaries SI, accompanied by calls for clearly defined metrics to evaluate SI efforts. In this review, we present the current state of the literature in regards to SI metrics. We first survey the literature to identify key concepts and qualities associated with SI (referred to as SI indicators). We briefly discuss indicators that have been sources of contention in the SI literature, and highlight tradeoffs between certain SI indicators. The bulk of this review focuses on identifying measurable properties (referred to as SI metrics) associated with each SI indicator. We also identify metrics of broader system-level properties such as sustainability and intensification. We conclude by highlighting gaps in the current literature on SI metrics.